Adaptive reuse of industrial heritage in Łódź as a tool for reintegrating urban spatial structure - Baranowska-Deptuła, Magdalena. Autor (IGiPZ PAN, 2025)
The research paper investigates the state of preservation of industrial heritage in Łódź, with a focus on its adaptive reuse and its significance in urban renewal processes. The study primarily explores projects carried out in pre-war factory areas during the post-transformation period, marked by the city’s rapid deindustrialisation. This economic shift, accompanied by social turbulence, contributed to serious spatial problems within the urban structure. Abandoned factory buildings have shaped degraded urban areas, often becoming sources of spatial exclusion and, in some cases, forming physical barriers that disconnected entire inner-city blocks from the active urban fabric. The research was conducted between April 2024 and April 2025 using qualitative methods, including fieldwork and on-site analysis of 287 post-industrial sites. The analysis of adaptive reuse directions of post-industrial heritage enables drawing more general conclusions regarding the revitalisation of such sites. Selected examples illustrate a range of new functions introduced into former factory spacesand evaluate which solutions are most effective in restoring spatial coherence and reintegrating fragmented areas within the city
24 cm
Keywords: post-industrial heritage; adaptive reuse; urban regeneration; revitalisation; spatial integration; Łódź